The Green Technology Practices and Investments of Sipalay City Beach-Resorts - MALACAPAY, Marjon C.; TABABA, Reynaldo (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020DO - 10.14505//jemt.v11.7(47).12, 2020)
The study of exploring the green technology practices and investments of beach-resorts in Sipalay City, Negros Occidental, Philippines, was realized in support of the worldwide call of promoting responsible and sustainable ecotourism sites. It discloses how these six resorts use green products in their operations, manage their waste, energy, and water resources, uncover practices that need improvement, including its primary causes, and evaluate their green technology investments' progress. This study is qualitative and designed as a multiple case study. Data were collected and validated through methodological triangulation (interview, document analysis, and on-site validation) and analyzed using Qualitative Data Analysis (QDA). Thus, notable findings include the resorts' use of stainless in replacement to plastic straws, glasses instead of disposable cups, and paper instead of Styrofoam boxes. Hence, the absence of compost pitting, the lack of a water control system, and the undersupply of solar panels are a few of the resorts' drawbacks. Therefore, this study discerns that the disproportion between capital and return of investments and the guests' lodging behavior influences the resorts' green technology practices and investments.